Photodissociation Dynamics of Cyclopropenylidene, c‐C3H2. Issue 41 (19th August 2015) - Schuurman, Michael S.; Giegerich, Jens; Pachner, Kai; Lang, Daniel; Kiendl, Benjamin; MacDonell, Ryan J.; Krueger, Anke; Fischer, Ingo
Abstract In this joint experimental and theoretical study we characterize the complete dynamical "life cycle" associated with the photoexcitation of the singlet carbene cyclopropenylidene to the lowest lying optically bright excited electronic state: from the initial creation of an excited‐state wavepacket to the ultimate fragmentation of the molecule on the vibrationally hot ground electronic state. Cyclopropenylidene is prepared in this work using an improved synthetic pathway for the preparation of the precursor quadricyclane, thereby greatly simplifying the assignment of the molecular origin of the measured photofragments. The excitation process and subsequent non‐adiabatic dynamics have been previously investigated employing time‐resolved photoelectron spectroscopy and are now complemented with high‐level ab initio trajectory simulations that elucidate the specific vibronic relaxation pathways. Lastly, the fragmentation channels accessed by the molecule following internal conversion are probed using velocity map imaging (VMI) so that the identity of the fragmentation products and their corresponding energy distributions can be definitively assigned.